Hyperuricemia as a Predictor of Poor Fetal Outcome in Pre-Eclamptic Women - AneelaKhaleeq , Khadija Waheed , Sara Ejaz , Ahmad Kamal (Journal of Rawalpindi Medical College, 2015)
Background:To evaluate the relation between raised serum uric acid level and fetal outcome. Methods:This Cohort study was conducted at Department of Obstetrics and Gynaecology, Services Hospital, Lahore, to compare the risk of poor fetal outcome in hyperuricemic and normouricemic pre-eclamptic patients. A total of 300 patients with the diagnosis of pre-eclampsia were included in the study and serum uric acid levels were obtained in all the patients. They were divided into two groups: Group A: Pre-eclamptic Normouricemic; Group B: Pre-eclamptic Hyperuricemic. All patients were followed after delivery for fetal outcome and results were compared in both groups. Results: The mean maternal age was 28.60 ± 3.308 years. The mean gestational age was 36.85 ± 0.59 weeks. The mean uric acid level of the patients at presentation was 5.067 ± 1.74 mg/dl. The mean uric acid level in group A was 3.64 ± 0.73 mg/dl and in group B was 7.98 ± 0.85 mg/dl. In group A, 9.3% newborns were found small-for-gestational-age (SGA), whereas in Group B, 23.3% newborns were found having SGA. The relative risk was calculated for development of SGA in hyperuricemia and was found significant (RR=2.5; 95% CI: 1.40- 4.45). Conclusion: Serum uric acid level measurement is a useful and inexpensive marker for predicting pre-eclampsia and fetal growth retardation in women presenting with gestational hypertension.